Investigation regarding the application of the titanium electrode for the water treatment plant in a steel manufacturing plant - Gradinac, Jovana; Jovović, Aleksandar (Frontiers in Chemistry, 2022)
Hard water causes problems in the industry since deposits inside pipes and equipment lead to lower plant efficiency and electricity costs. The growing demands for high-quality water necessitate the development of modern and cost-effective technologies for softening very hard waters. One of these techniques is the electrocoagulation process (EC). This study aimed to examine the effectiveness of the electrocoagulation (EC) process for removing scale ions in water using titanium rod electrodes. The research was carried out on pilot electrodes. Results that were obtained, have focused to show the effectiveness and efficiency of the application of titanium electrodes for removing hardness from makeup and process water inside a closed system, utilizing a Universal Environmental Technologies system (UET system). The plant consisted of a heat pump, a heat exchanger, a cooling tower, and a UET reactor with a titanium rod.